1-[5-(4-Bromophenyl)-3-(4-fluorophenyl)-4,5-dihydro-1H-pyrazol-1-yl]butan-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title compound, C(19)H(18)BrFN(2)O, the benzene rings form dihedral angles of 5.38 (7) and 85.48 (7)° with the mean plane of the 4,5-dihydro-1H-pyrazole ring (r.m.s. deviation = 0.0849 Å), which approximates to an envelope conformation with the –CH(2)– group as the flap. The dihedral angle between the benzene rings is 82.86 (7)°. In the crystal, C—H⋯F and C—H⋯O hydrogen bonds link the molecules to form inversion dimers and together these generate chains along [011]. The crystal packing also features C—H⋯π interactions.